Growth for the Bottom 40 Percent : The World Bank Group’s Support for Shared Prosperity - Independent Evaluation Group (World Bank, Washington, DC, 2017)
This evaluation assesses the World Bank Group's record on implementation of the shared prosperity goal since 2013 using the official definition of the goal of fostering income growth of the bottom 40 percent. It also analyzes institutional requirements for effective implementation of the goal, and assesses the extent to which the Bank Group was already incorporating distributional issues in its various activities during the period 2005-13, before the adoption of the goal.Principal conclusions are as follows. The World Bank Group has made a significant effort to incorporate the shared prosperity goal—since its introduction in 2013--into its various products and services, across regions, global practices and World Bank Group institutions. These efforts have been spearheaded by knowledge. And the World Bank Group has used its convening power and partnerships at global and country levels to boost shared prosperity. However, an increased focus on distributional issues in the World Bank’s lending projects does not automatically lead to improved development outcomes. Greater efforts are needed in the following areas to translate the increased focus into strong development results. First, the World Bank Group strategies and projects should have well-defined theories of change that explain how and under what conditions its interventions are expected to lead to improved shared prosperity outcomes. Second, associated results frameworks should allow for adequately monitoring impacts on the bottom 40 percent, and more distributional data should become available for measuring World Bank contributions. Third, strong analytical underpinnings are critical to strengthening the design of shared prosperity–focused interventions. This requires ensuring adequate funding of knowledge work and rigorous analysis of distributional effects. Fourth, the report recommends that the World Bank Group monitors systematically spatial congruence of its projects with the geographic distribution of the bottom 40 percent populations.Finally, stronger efforts are needed to make sure that the World Bank Group staff are aware of what the shared prosperity goal entails for the institution and its clients, but also have the skills needed for effectively incorporating and monitoring distributional objectives in the result chains of World Bank Group strategies and projects.